Blade Deterioration in a Gas Turbine Engine - W. Tabakoff; A. Hamed; V. Shanov (International Journal of Rotating Machinery)
A study has been conducted to predict blade erosion of gas turbine engines. The blade material erosion model is based on three dimensional particle trajectory simulation in the three-dimensional turbine flow field. The trajectories provide the special distribution of the particle impact parameters over the blade surface. A semi-empirical erosion model, derived from erosion tests of material samples at different particulate flow conditions, is used in the prediction of blade surface erosion based on the trajectory impact data. To improve the blade erosion resistance and to decrease the blade deterioration, the blades must be coated. For this purpose, an experimental study was conducted to investigate the behavior of rhodium platinum aluminide coating exposed to erosion by fly ash particles. New protective coatings are developed for erosion and thermal barrier. Chemical vapor deposition technique (CVD) was used to apply the ceramic TiC coatings on INCO 718 and stainless steel 410. The erosive wear of the coated samples was investigated experimentally by exposing them to particle laden flow at velocities from 180 to 305m/s and temperatures from ambient to 538°C in a specially designed erosion wind tunnel. Both materials (INCO 718 and stainless steel 410) coated with CVD TiC showed one order of magnitude less erosion rate compared to some commercial coatings on the same substrates.